Studi Numerik Gerakan Mainan Mekanik Monobike - Eva Hertnacahyani Herraprastanti; Hendri Suryanto .; Suluh Jatmiko . (SIMETRIS, 2019)
In today's development where there are several applications to design a product, where in the design of a product, not only can physically design the components, but also can design the desired movements. In order to produce product movements as desired, when designing it must first choose the right mechanism and perform synthesis and analysis of kinematics. To make a toy move, the components which make up the toy are needed by following a certain mechanism. In this study the mechanical toy that will be analyzed for its movements is Monobike. In the monobike there is a Slider Crank mechanism that results from the paddling of the foot which rotates the pedal and moves up and down. The up and down pedal will turn the second wheel and cause the body of the doll holding the fan to move up and down. The research objective is to numerically analyze component movements in Monobike mechanical toys which include linear displacement, velocity and acceleration analysis. In this research, a monobike mechanical toy that mimics human activities in pedaling a bicycle is determined. The methodology in this research is as follows: a) make a kinematic diagram, b) determine the position vector of each link, c) derive the equation, d) make the GNU Octave code. Based on the results of the study concluded that a numerical study with the GNU Octave can be done to analyze the kinematic motion of a machine. Linear displacement on link 3 has the furthest displacement of 18.38 mm, and one cycle of movement requires 120 seconds. The maximum linear speed of the Monobike mechanical toy is 36.2 mm / sec. While the maximum linear acceleration of a monobike mechanical toy is 172.3 mm / sec. GNU Octave is a freeware application that is no less reliable than the Matlab application in analyzing the kinematics of a machine.